PREVALENCE AND RISK FACTORS OF OVERWEIGHT AND OBESITY IN TURKISH ACADEMIC STAFF - Pirincci, Edibe; Rahman, Sueheyla; Durmus, Birsen; Acik, Yasemin (Southeast Asian Ministers Educ Organization, 2009)
Obesity and overweight are a significant public health problem that affects the quality of life of the individuals concerned. We studied the prevalence and related risk factors for obesity among academics. This descriptive cross-sectional study sampled 499 academic staff at Elazig Firat University, Turkey. Height, weight and blood pressure values were obtained and a descriptive survey was conducted. The age range of the participants was 22 to 65 years, with a mean age 36.5 +/- 8 1 years. The group had 29% women, and 71% men; 80% were married. The mean BMI of the participants was 24.6 +/- 3.1 kg/m(2) Their mean systolic blood pressure was 117.0 +/- 12.1 mmHg and mean diastolic blood pressure was 73.1 +/- 8.0 mmHg. The overall prevalence of obesity was 7.0%; 2.1% in women and 9.0% in men The combined prevalence of overweight and obesity was 45.9%, Nearly half the participants were either obese or overweight. A correlation was identified between overweight/obesity and sex, marital status, academic staff, physical activity, systolic and diastolic blood pressure. Although the study did not include all academics, the results reveal the need to evaluate the health impact of obesity in academics.
Keywords: Life-Style; Population; Weight; Adults